If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4.5 + m) + 3 = 4(m + -3) * 5.5 (4.5 * 2 + m * 2) + 3 = 4(m + -3) * 5.5 (9 + 2m) + 3 = 4(m + -3) * 5.5 Reorder the terms: 9 + 3 + 2m = 4(m + -3) * 5.5 Combine like terms: 9 + 3 = 12 12 + 2m = 4(m + -3) * 5.5 Reorder the terms: 12 + 2m = 4(-3 + m) * 5.5 Reorder the terms for easier multiplication: 12 + 2m = 4 * 5.5(-3 + m) Multiply 4 * 5.5 12 + 2m = 22(-3 + m) 12 + 2m = (-3 * 22 + m * 22) 12 + 2m = (-66 + 22m) Solving 12 + 2m = -66 + 22m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-22m' to each side of the equation. 12 + 2m + -22m = -66 + 22m + -22m Combine like terms: 2m + -22m = -20m 12 + -20m = -66 + 22m + -22m Combine like terms: 22m + -22m = 0 12 + -20m = -66 + 0 12 + -20m = -66 Add '-12' to each side of the equation. 12 + -12 + -20m = -66 + -12 Combine like terms: 12 + -12 = 0 0 + -20m = -66 + -12 -20m = -66 + -12 Combine like terms: -66 + -12 = -78 -20m = -78 Divide each side by '-20'. m = 3.9 Simplifying m = 3.9
| 2x+-1-6=10+-10x+6 | | 12d+5e-7d= | | 1=4.5-2p+2.333333p | | 5k(k-2)-8k=-34 | | 1+x-6x=11 | | 5x=2x+42 | | 4p+8p-p= | | -7y=9-10y | | -5t-4=2t+14 | | 5x+1y=112 | | 1.25x=15.25 | | 6w+12=48 | | (5x-2)(3x+4)=(3x-5)(5x+1)+15 | | 4x+152=6x+166 | | 4k^2+3k-7=0 | | 9p+5q-2p= | | X-3+8=20 | | 3p+9=6p | | 5x-4+3=19 | | 5b-12b-90= | | 4k^2+11k+7=0 | | -7-3k=-4k | | 7j+4j+7k= | | -4t-7t= | | 360=x+7+2x-1 | | 4x+8=9x-7 | | 1/7-t/7=-5/7 | | -2(18-3x)=7y+2y | | 180=x+5+x+6+x+7 | | 9-6*x=-15 | | 18p=8 | | 75(2x-3)-1=5 |